Síndrome de fragilidad en adultos jóvenes con enfermedades crónicas: un desafío silencioso para la medicina interna - Sánchez Blanco, Lázaro Alejandro; Gavilán Naranjo, Arianna María (EsTuSalud, 2025)
Frailty has traditionally been conceptualized as a geriatric syndrome, characterized by the progressive loss of physiological and functional reserve, which increases the individual's vulnerability to adverse events. However, in recent years, emerging studies have revealed a new clinical reality: frailty can manifest in young adults, especially those living with chronic inflammatory or degenerative diseases.